Supply chain risk management : a case study of PT. Mirota Inah Indonesia - Lee, Hsun Yee (2014)
The purpose of the study is to carry out the real situation of the company and provide strategies after identify the potential risks along the supply chain. The study is conducted through the semi-structured interview, document reviewed and factory visit. The SWOT and TOWS analysis of the company has been identified. Besides that, several risks also recognized along the supply chain that impact their business. After the analysis, several recommendations are given to the company to improve the current situation, such as build a proper risk assessment and improve in quality control. The main concern drawn down in this study is that the current approaches of the company are unable to confront the uncertainties.